Electrocautery versus cold steel tonsillectomy comparison study - Abdul Aema, Firas Baheej (AL-Kindy College Medical Journal, 2019)
Objective: the objective of this study was to compare the intraoperative blood loss, intraoperative time, postoperative pain and secondary hemorrhage between electrodissection and cold steel dissection tonsillectomy. Methods: One hundred and six patients were enrolled in this study, the patients were randomly allocated into electrodissection group A (n=51) and cold steel dissection tonsillectomy group B (n=53). All patients are above 7 years and had history of recurrent tonsillitis and/or tonsillar hypertrophy with obstructive symptoms. Intraoperative parameters and postoperative outcome were assessed. Results: In group A patients had statically significant less operative time and blood loss than group B early postoperative pain was not differ significantly between the two groups, however late onset pain (pain on the 7th day) was significantly higher in group A. There was no significant difference between the groups regarding secondary hemorrhage. Conclusion: Electrodissection tonsillectomy is rapid, safe and effective method of tonsillectomy with obvious advantage of minimum perioperative blood loss, lower operative time and without early post-operative pain difference when compared to cold steel dissection tonsillectomy. Although it has some disadvantage of late postoperative pain.